ESO (Journal of Parents and Teachers, 2014)
The article is structured in the form of a guide detailing information about the Compulsory Secondary Education stage in Spain. In this way, the author includes sources of interest and resources to navigate about the legislative and didactic framework of this stage.
Keywords: library and education; library pym; Secindary education; Educational resources